Immunochemical relationship of the major outer membrane protein of Rhodopseudomonas sphaeroides 2.4.1 to proteins of other photosynthetic bacteria. - Deal, C D (1983)
Immunoblots of sodium dodecyl sulfate-polyacrylamide gels derived from outer membrane preparations of various strains of Rhodopseudomonas sphaeroides revealed polypeptides which cross-reacted with antibody directed against the major outer membrane protein of R. sphaeroides 2.4.1. Immunochemical quantitation of the major outer membrane protein of strain 2.4.1 showed approximately 5.5 x 10(4) molecules per cell whether cells were grown chemoheterotrophically or photoheterotrophically. Rhodospirillum rubrum outer membranes contained a cross-reactive protein, whereas the outer membranes derived from Rhodopseudomonas capsulata and Paracoccus denitrificans showed no cross-reaction with the antibody prepared against the major outer membrane protein from R. sphaeroides 2.4.1.